2022
DOI: 10.1002/jso.27013
|View full text |Cite
|
Sign up to set email alerts
|

Extensive open lobectomy experience is not a prerequisite for learning uniportal video‐assisted thoracic surgery lobectomy

Abstract: Background and objectives: Uniportal video-assisted thoracoscopic surgery (U-VATS) lobectomy has been increasingly adopted to manage early stage lung cancer. However, little information is available on whether this technique can be taught to surgeons inexperienced in open lobectomy. This study aimed to investigate the learning curve for U-VATS lobectomy performed by a single surgeon with limited open lobectomy experience.Methods: From July 2018 to September 2020, 103 patients received U-VATS lobectomy for lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…So far, only Zhai et al [ 12 ] reported a complication-based learning curve. Our reported number of cases required before a significant decrease in technique-related complications is shown (between 50 and 96 procedures), is in agreement with the 61 procedures as the initial learning phase of a single surgeon with limited open lobectomy experience published by Zhai et al [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…So far, only Zhai et al [ 12 ] reported a complication-based learning curve. Our reported number of cases required before a significant decrease in technique-related complications is shown (between 50 and 96 procedures), is in agreement with the 61 procedures as the initial learning phase of a single surgeon with limited open lobectomy experience published by Zhai et al [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…So far, only Zhai et al [ 12 ] reported a complication-based learning curve. Our reported number of cases required before a significant decrease in technique-related complications is shown (between 50 and 96 procedures), is in agreement with the 61 procedures as the initial learning phase of a single surgeon with limited open lobectomy experience published by Zhai et al [ 12 ]. Whereas Zhai et al performed a learning curve on surgical failures which also included pneumonia, cardiac complications, subcutaneous emphysema, delirium, less than 10 harvested lymph nodes , and 30-day readmissions, we performed a complication-based learning curve on predefined technique-related complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation